ANALISIS PENGARUH KOMITMEN ORGANISASIONAL DAN KEPUASAN KERJA TERHADAP KINERJA KARYAWAN (Studi pada PT. SINAR SOSRO Semarang) - Priyatama, Aldo; Rahardja, Edy (Faculty of Economics and Business Diponegoro University, 2014)
The purpose of the study is to answer organizational commitment and job satisfaction influence on performance. The samples were employees of PT. SINAR SOSRO Semarang where the number of samples specified in this study of 81 respondents. As for the methods used in this sampling is to use Purposive sampling, while data analysis method used is linear regression analysis, with the aid of SPSS program.Results of testing of the hypothesis, suggesting that the variables: 1). Organizational commitment has no significant effect on performance, 2). Job satisfaction significant on employee performance. Coefficient of determination results indicate that the ability of small organizational commitment and job satisfaction variables in explaining employee performance variables is very limited.